2018
DOI: 10.1111/apa.14431
|View full text |Cite
|
Sign up to set email alerts
|

Smoking in pregnancy is a key factor for sudden infant death among Māori

Abstract: The association between known SUDI risk factors, including bed sharing and/or smoking in pregnancy and SUDI risk, is the same regardless of ethnicity. Māori infants are exposed more frequently to both behaviours because of the higher Māori smoking rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 12 publications
2
14
1
Order By: Relevance
“…There are known difficulties in recruiting controls from groups with greater risks and lower socio-economic status, 5 would make undertaking a case-control study in Queensland, difficult, time-consuming and very costly.…”
Section: Limitationsmentioning
confidence: 99%
“…There are known difficulties in recruiting controls from groups with greater risks and lower socio-economic status, 5 would make undertaking a case-control study in Queensland, difficult, time-consuming and very costly.…”
Section: Limitationsmentioning
confidence: 99%
“…A case–control study by MacFarlane et al. showed that the association between known SUDI risk factors such as smoking in pregnancy and bed sharing, and SUDI risks were the same regardless of ethnicity. However, the Maori infants were exposed to both behaviours more frequently.…”
Section: Smoking In Pregnancy Is Linked To High Maori Sudden Unexpectmentioning
confidence: 99%
“…The SUDI mortality rate for Māori was 1.4 per 1000 live births compared to 0.5/1000 for non‐Māori. The overall SUDI rate was 0.8/1000 .…”
mentioning
confidence: 94%
“…SUDI rates for Māori have decreased, partly due to a successful Safe Sleep Programme , but remain higher than for the non‐Māori population. In this issue of Acta Paediatrica , MacFarlane et al address the question why the SUDI incidence is so high among Māoris. Half of the SUDI cases in New Zealand between 2012 and 2015 were Māori, despite that Māori comprise less than a third of live births in the country.…”
mentioning
confidence: 99%